Preparation and Characterization of PMMA and its Derivative via RAFT Technique in the Presence of Disulﬁde as a Source of Chain Transfer Agent - Li, Juan; Jiang, Ting-Ting; Shen, Jiang-nan; Ruan, Hui-Min (Journal of Membrane and Separation Technology, 2012)
Poly(methyl methacrylate) (PMMA) were synthesized by using chain transfer agents(CTA), S-1-Dodecyl-S′-(α,α′-dimethyl-α-acetic acid) trithiocarbonate (MTTCD), S,S′-bis (2-hydroxyethyl-2′-dimethylacrylate) trithiocarbonate (BDATC), 2-cyanoprop-2-yl dithiobenzoate (CPDB) respectively, through the reversible addition fragmentation chain transfer (RAFT) polymerization under a range of synthesis conditions. The results indicated that the structure of the end-group of RAFT agents had signiﬁcant effects on the ability to control polymerization. Compared with MTTCD and CPDB, BDATC can provide better control over the relative molecular mass, distribution and polymerization of PMMA. The derived well-controlled block copolymer PMMA-b-PDMAEMA and PMMA-b-PDMAEA were also successfully prepared by using N, N-dimethylaminoethy acrylate (DMAEA) or N, N-dimethylaminoethyl methacrylate (DMAEMA) as the second monomer. The chemical composition and structure of the products were characterized by FTIR, 1HNMR, XRD and DSC. CO2 and N2 permeation performance of the PMMA-b-PDMAEA/PS composite membranes were tested at different pressure. The results showed that the resulted composited membrane had a CO2 permeation rate of 3.68×10-5cm3 (STP) cm-2s-1cmHg-1, a N2 permeation rate of 1.78×10-7 cm3 (STP) cm-2s-1cmHg-1 and an ideal CO2/ N2 selectivity of 206.6 at a feed gas pressure of 7.6 cmHg and 30 oC.